IN-VITRO CULTURE FOR REGENERATION OF Melia azedarach L. USING AGITATED LIQUID MEDIUM - Nirsatmanto, Arif (Secretariat of Forestry Research and Development Agency, 2006)
This study investigated the applicability of liquid medium in direct organogenesis of in-vitro culture of Melia azedarach L. Explants were collected from in-vitro multiplication originating from aseptically germinated seedling and from a 48 - years old mature tree. For adventitious shoot differentiation, 2 mm length of excised explants were cultured on liquid medium of MS (Murashige and Skoogs) basal medium supplemented with 28 combinations of hormone BAP (6-benzylaminopurine) and NAA (á- naphthaleneacetic acid). Differentiated shoots were subsequently cultured for shoot elongation in solid medium using MS basal medium supplemented with hormone BAP individually as well as in combinations with NAA. Finally, rooting culture were done using MS medium supplemented with IBA (3 indolebutyric acid). The results showed that the rate of shoot organogenesis of M. azedarach could be obtained through agitated liquid medium culture technique. The combination of hormone BAP 0.1-1 µM and NAA 0.01-0.1 µM are induced more adventitious shoot at a rate of 5 shoots / 2 mm length size of explants are transferring into rooting medium containing IBA 4.92 µM.